2014
DOI: 10.1097/opx.0000000000000275
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront-Guided Scleral Lens Correction in Keratoconus

Abstract: Purpose To examine the performance of state-of-the-art wavefront-guided scleral contact lenses (wfgSCLs) on a sample of keratoconic eyes, with emphasis on performance quantified with visual quality metrics; and to provide a detailed discussion of the process used to design, manufacture and evaluate wfgSCLs. Methods Fourteen eyes of 7 subjects with keratoconus were enrolled and a wfgSCL was designed for each eye. High-contrast visual acuity and visual quality metrics were used to assess the on-eye performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 41 publications
(39 reference statements)
5
65
1
Order By: Relevance
“…In particular, we outline the literature that has demonstrated the limitations associated with aberration-controlled soft contact lens designs and the need for further work to validate the clinical feasibility of such modalities for the management of keratoconus. Although still currently limited to the research domain and not yet directly applicable to managing patients in clinical practice, we agree with the sentiment that customised aberration-controlled scleral lenses 2,3 show promise as a potential future vision-correction platform for keratoconus. In a small population of seven individuals with keratoconus, Marsack and colleagues 2 have shown that wave-front guided scleral contact lenses can optically compensate for higher-order aberrations; however, as these authors note, 2 a range of factors will need to be surmounted in order for the custom correction of highly aberrated eyes to achieve clinical translation.…”
Section: Editorsupporting
confidence: 54%
See 1 more Smart Citation
“…In particular, we outline the literature that has demonstrated the limitations associated with aberration-controlled soft contact lens designs and the need for further work to validate the clinical feasibility of such modalities for the management of keratoconus. Although still currently limited to the research domain and not yet directly applicable to managing patients in clinical practice, we agree with the sentiment that customised aberration-controlled scleral lenses 2,3 show promise as a potential future vision-correction platform for keratoconus. In a small population of seven individuals with keratoconus, Marsack and colleagues 2 have shown that wave-front guided scleral contact lenses can optically compensate for higher-order aberrations; however, as these authors note, 2 a range of factors will need to be surmounted in order for the custom correction of highly aberrated eyes to achieve clinical translation.…”
Section: Editorsupporting
confidence: 54%
“…Although still currently limited to the research domain and not yet directly applicable to managing patients in clinical practice, we agree with the sentiment that customised aberration-controlled scleral lenses 2,3 show promise as a potential future vision-correction platform for keratoconus. In a small population of seven individuals with keratoconus, Marsack and colleagues 2 have shown that wave-front guided scleral contact lenses can optically compensate for higher-order aberrations; however, as these authors note, 2 a range of factors will need to be surmounted in order for the custom correction of highly aberrated eyes to achieve clinical translation. Such factors include the complexity of fitting (and the need for highly repeatable centration), the current cost of the devices (to patient and practitioner) and longer-duration studies to assess real-world effects on visual performance.…”
Section: Editorsupporting
confidence: 54%
“…10,11 However this level of performance requires that the wavefront-guided correction remain aligned with the underlying WFE of the eye. Here three separate stabilization designs (DTLD, DTSC and DTBSC) were evaluated and compared to the traditional spherical lens with no stabilizing methods (SLD).…”
Section: Discussionmentioning
confidence: 99%
“…10,11 However, unlike a typical scleral contact lens intended to correct defocus, a wavefront-guided contact lens must remain well-aligned to the underlying optical components of the eye. 12-15 Failure to align a wavefront-guided correction (which incorporates higher order aberration compensation in addition to the sphero-cylindrical correction) leads to the induction of complex, unintended wavefront errors that, depending on their magnitude, can be optically devastating.…”
Section: Introductionmentioning
confidence: 99%
“…18 Furthermore, large scleral lenses with excellent positional stability on the eye are being used to correct ocular aberrations. 19 Intraocular lenses (IOLs) are routinely used to replace the natural crystalline lens following cataract surgery. These lenses may also benefit from wavefront correction.…”
Section: Custom Ophthalmic Lensesmentioning
confidence: 99%